Evaluation of knowledge and barriers of influenza vaccine uptake among university students in Saudi Arabia; a cross-sectional analysis - Tauqeer Hussain Mallhi; Nida Bokharee; Munnaza Bukhsh; Yusra Habib Khan; Abdulaziz Ibrahim Alzarea; Faiz Ullah Khan; Salah-Ud-Din Khan; Nasser Hadal Alotaibi; Abdullah Salah Alanazi; Muhammad Hammad Butt; Ahmed D. Alatawi; Muhammad Shahid Iqbal (PeerJ, 2022)
Background Influenza vaccine hesitancy is a significant threat to global maneuvers for reducing the burden of seasonal and pandemic influenza. This study estimated the vaccine uptake, barriers, and willingness for influenza vaccines among university students in Saudi Arabia. Methods A cross-sectional survey was conducted among health science (HS) and non-health science (NHS) university students. A 31-item questionnaire was used to ascertain the vaccination rate, barriers, and willingness for the flu vaccine. Results This study included 790 students (mean age: 21.40 ± 1.94 years), 246 (31.1%) from HS and 544 (68.9%) from NHS disciplines. About 70% did not take flu shots before the arrival of the winter. The mean knowledge score was 7.81 ± 1.96, where 20.4%, 67.6%, and 12% of respondents had good, moderate, and poor knowledge regarding flu vaccines. The relative importance index (RII) analysis showed a lack of recommendation from physicians (51.5%, RI ranked: 1) was a top-ranked barrier to vaccine uptake, followed by negative perceptions and accessibility issues. Only 36.6% of the participants were willing to get vaccinated every year, 70% were willing to receive a vaccine on their doctor’s recommendations, and 46% agreed to vaccinate if vaccines were freely available in the university. The knowledge, barriers, and willingness widely varied across students from two disciplines. Conclusions Our analysis underscored low flu vaccine uptake among university students. In addition, the study participants’ knowledge was unsatisfactory, and they were less inclined to receive the flu vaccine in the future. Lack of recommendation from the physicians, negative perceptions towards the flu vaccine, and difficult accessibility were found as significant barriers to the vaccine uptake. A multidimensional approach at educational institutes to cover the knowledge gap and address the barriers curtailing the vaccination rate among students is recommended.